PERENCANAN AGENDA BERITA BERORIENTASI KESEHATAN LINGKUNGAN PENGALAMAN DARI PERISTIWA PANDEMI COVID-19 - Syaiful Bachri; Sitti Mirsa; Zulkarnain Hamson; Herawaty Herawaty; Lorensius Lonik (Yayasan Education and Social Center, 2023)
News planning is the process of planning and managing all aspects of news production. It involves the steps an editor, reporter or editorial team takes to decide on the topic, story, sources, style and format to use in preparing the story. The goal of news planning is to ensure that news is presented in a way that is clear, accurate, balanced and attractive. The news agenda refers to the list of topics or issues that the media chooses to cover in a certain period of time. The focus of health news refers to the approach or point of view taken in preparing and covering health issues. Health news can cover a wide range of topics, from the latest medical developments, health policy issues, healthy lifestyles, medical research, pandemics, medicines, and more. This Community Service (PKM) was carried out by a combination of lecturers from two private universities (PTS), after observing the Covid-19 Pandemic and its impact on society. Held at the People's Editorial Office of New Makassar City, against journalists and editors. There were obstacles related to the busyness of the editors, but managed to provide an understanding of the importance of news in maintaining environmental health for the editors